Evaluation of TLC-NOSF dressing with poly-absorbent fibres in exuding leg ulcers: two multicentric, single-arm, prospective, open-label clinical trials. (3rd March 2019) - Sigal, Michèle-Léa; Addala, Azeddine; Maillard, Hervé; Chahim, Maxime; Sala, Florent; Blaise, Sophie; Dalac, Sophie; Meaume, Sylvie; Bohbot, Serge; Tumba, Clémence; Tacca, Olivier
Abstract : Objective: To assess the efficacy, safety and acceptability of a new TLC-NOSF dressing with poly-absorbent fibres in the management of exuding leg ulcers, at the different stages of healing. Method: This work presents the results of two prospective, multicentric clinical studies: NEREIDES and CASSIOPEE. Patients with a non-infected, moderate-to-strongly exudating leg ulcer of venous or mixed origin, were treated with the dressing and an appropriate compression system for 12 weeks. The wounds included in NEREIDES had to be in debridement stage, and those in CASSIOPEE at granulation stage. In both studies, the primary outcome was the relative wound area reduction (RWAR) at week 12. Main secondary outcomes included healing rate, time-to-reach wound closure, adverse events and acceptability of the dressing by patients and health professionals. Results: There were 37 patients included in NEREIDES and 51 in CASSIOPEE. The two cohorts presented similar patient and wound characteristics, except from the percentage of sloughy tissue on wound bed at baseline (median: 75% NEREIDES and 30% CASSIOPEE). At week 12, the RWAR (60% NEREIDES and 81% CASSIOPEE), wound closure rates (18% NEREIDES and 20% CASSIOPEE) and mean times-to-reach wound closure (58±27 days NEREIDES and 55±23 days CASSIOPEE) supported the beneficial outcomes of the treatment in both cohorts. In patients with a wound duration ≤6 months, the wound area reduction reached 85% in NEREIDES and 81% in CASSIOPEE, highlighting the importance to initiate adequate treatment as soon as possible. The nature and frequency of the local adverse events were similar in both studies and consistent with the good safety profiles of the poly-absorbent fibres and of the TLC-NOSF dressings. The acceptability of the dressing (easy to apply, conformable and non-adherent to the wound bed at removal, with no pain or bleeding at removal) has been judged 'very good' or 'good' at each stage of the healing process, by both nursing staff and patients. Conclusion: These clinical results establish the new TLC-NOSF dressing with poly-absorbent fibres (UrgoStart Plus, Laboratoires Urgo) as an effective, safe and simple treatment for the local management of leg ulcers, at the different stages of healing and until wound closure.